IMPLEMENTASI LAYANAN PUBLIK BERBASIS SMART GOVERNANCE: STUDI KASUS PROGRAM GEULIS DI KOTA BANDUNG - Allyah Nur Rahmani; Dhinda Dwi Maharani; Najwa Auliya Syarifah; Ivan Darmawan (Triwikrama: Jurnal Ilmu Sosial, 2024)
Public service is a duty of the government and its apparatus to fulfill the basic needs of its citizens who have fulfilled their obligations as citizens. Thus, public service from the perspective of citizens is a "right," while public service from the perspective of the government and its apparatus is an "obligation." In this paper, the author will discuss public services provided by the Bandung City Population and Civil Registry Department in collaboration with the Bandung City's Local People's Representative Council, namely the Geulis service. The method used by the author is a literature study method which is gathering data from the internet and journal articles. In this writing, the author aims to understand the implementation of Geulis in Bandung City within the context of Smart Governance. The results obtained in this paper show that with the development of technology in society, public services must also be accompanied by the development of technology. With the Geulis, it is hoped that the Population and Civil Registry Department can serve the people in Bandung City much better.